2021
DOI: 10.1002/ehf2.13511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous furosemide plus small‐volume hypertonic saline solutions on markers of heart failure

Abstract: AimsWe sought to compare the effects of furosemide + hypertonic saline solution (HSS) treatment in patients with acute decompensated heart failure in comparison with furosemide alone and the response in a compensated state after an acute saline load with regard to serum levels of heart failure biomarkers. Methods and resultsWe enrolled 141 patients with acute decompensated heart failure with reduced ejection fraction admitted to our Internal Medicine ward from March 2017 to November 2019. A total of 73 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…The concentration of proinflammatory cytokines, i.e., TNFα and IL-6 measured in supernatants of human peripheral blood mononuclear cells of a patient with chronic heart failure were inhibited in a dose-dependent manner by furosemide treatment [ 19 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of proinflammatory cytokines, i.e., TNFα and IL-6 measured in supernatants of human peripheral blood mononuclear cells of a patient with chronic heart failure were inhibited in a dose-dependent manner by furosemide treatment [ 19 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, association between loop diuretics and hypertonic saline solutions in the management of heart failure and associated hyponatremia became an area of interest in many studies. Tuttolomondo A. et al, observed that administration of a high dose of furosemide in association with hypertonic saline solution led to a decrease in natriuretic peptide and cytokine plasma levels (TNF-α, IL-1β, IL-6) [ 53 ]. Griffin M. et al, made a retrospective analysis in patients receiving 150 mL of 3% NaCl over 30 min, administered simultaneously with high doses of loop diuretics.…”
Section: Treatment Of Dilutional Hyponatremiamentioning
confidence: 99%
“…Tuttolomondo A, et al [14] Effects of intravenous furosemide plus small-volume hypertonic saline solutions on markers of heart failure R: 141…”
Section: Kitzman Dw Et Al [213]mentioning
confidence: 99%